Amplitude and frequency spectrum of temporomandibular joint sounds from subjects with and without other signs/symptoms of temporomandibular disorders - Sano, T.; Widmalm, S.-E.; Westesson, P.-L.; Takahashi, K.; Yoshida, H.; Michi, K.; Okano, T. (Journal of oral rehabilitation, 1999)
Temporomandibular joint (TMJ) sound is one of the most commonly recognized signs in patients with temporomandibular disorders (TMD) but is also frequently seen in asymptomatic individuals. Sound recording is therefore only meaningful if the sounds from a normal healthy joint can be differentiated from those in patients. In this study, the amplitude and power spectrum of the TMJ sounds from symptomatic patients and asymptomatic individuals were recorded and compared. The result showed that TMJ sounds from symptomatic patients had a larger amplitude than sounds from asymptomatic subjects. A significant proportion of sounds had frequencies between 2000 and 3000 Hz. It was concluded that the characteristic amplitude is worthy of further study as a sign of possible diagnostic value. Secondly, the bandwidth of the sensors used at electronic TMJ sound recording should not be less than 3000 Hz.